Congruence of the Medical Record and Subject Interview on Time of Symptom Onset in Patients Diagnosed With Acute Coronary Syndrome. Issue 6 (November 2016) - Davis, Leslie L.; McCoy, Thomas P.; Riegel, Barbara; McKinley, Sharon; Doering, Lynn V.; Dracup, Kathleen; Moser, Debra K.
Abstract : Background: Past research has shown discrepancies between the time of symptom onset for patients with acute coronary syndrome (ACS) as documented in the medical record (MR) and patients' recall of the time assessed through subject interviews done later by researchers. Purpose: The aim of this study is to determine if there were differences between the time of symptom onset documented in the MR and subject interview taking into consideration sex, age group, and recall period for patients admitted to the emergency department for symptoms suggestive of ACS. Methods: A secondary analysis was conducted on data from the PROMOTION (Patient Response to Myocardial Infarction Following a Teaching Intervention Offered by Nurses) trial, a multicenter randomized clinical trial to reduce patient prehospital delay to treatment in ACS. Results: Of the 3522 subjects with CAD enrolled into the trial, 3087 subjects completed 2-year follow-up. Of these, 331 subjects sought treatment in the emergency department for ACS symptoms and 276 patients (83%) had complete information on the time of symptom onset from both sources. Of the 276 patients, 25 (9%) had differing times more than 48 hours and were thus excluded. The median difference between the 2 sources was 45.0 minutes. When both times were examined, there were no significant differences in time by sex (P = .720) or by age group (P = .188). The median number of days between the interview and the date of symptom onset was 29.5 days. There was a significant correlation between differences in the time of symptom onset and the length of recall period (rs = 0.148, P = .023). In multivariable modeling, a longer recall period was associated with greater median differences in the symptom onset time (b = 13.2, P = .023). Conclusion: These results suggest that the time of symptom onset obtained at the time of the index event and documented in the MR is not interchangeable with data obtained later by research staff, especially if the interview is not conducted near the time of the index event.